(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Fibroids are the most common benign tumours of smooth muscle cells of uterus in females and typically found during the middle and later reproductive years. As fibroid is an estrogen and progesterone dependent tumour, it gradually decreases in size during starting of menopause. The objective of this presented study was to determine management options among fibroid uterus patients. Methods: 50 number of patients were included in this study those whos age of 20-55, with symptomatic uterine fibroid and undergone hysterectomy or myomectomy. Postmenopausal, Pregnancy and Asymptomatic fibroid were excluded from this study. Results: The study showed that 52 percent of patient having fibroid uterus were belonged to 31-40 years of age. The mean age was 41.2±6.07. The majority 74% of patients in this study presented with menstrual abnormalities, 40% presented with abdominal lump. Dysmenorrhoea was 26%, 6% patient had primary subfertility and 14% secondary subfertility. Total Abdominal Hysterectomy (TAH) with unilateral salpingo- oophorectomy done in 10% cases, TAH with bilateral salpinooophorectomy in 22% cases, non descent vaginal hysterectomy in 6% cases, myomectomy done in 20% cases and polypectomy was done in 2% cases. Conclusion: Uterine fibroids are very common in women and frequently in late reproductive and perimenopausal years. It is also a common gynecological problem in our country, which frequently disturbs the lives of woman. Women now have choice of therapies for the treatment of fibroids. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 48-51